1248 "Passing the Surgical Torch"- A Review of Appropriate Surgical Handover Protocol on The Acute Surgical Take. (12th October 2021) - Shaladi, A; Marshall, K; Fernandes, R
Abstract: Aim: Effective handover between shifts is vital to protect patient safety. The Royal College of Surgeons has detailed the necessary information needed for each patient at handover. We aimed to assess compliance with this handover protocol. Method: Weekday surgical handover was reviewed over an 8-week period of time. Data was collected on documentation of diagnosis, up to investigations/bloods, clinical state of patient, management plan and resuscitation status/ceiling of care and COVID status. Results: 210 patients were reviewed. Of these, a clear diagnosis was documented for 152 patients. Up to date imaging results if applicable was documented in 111 of 153 patients. Up to date bloods were included in 140 of 210 patients. COVID status was only noted in 31 of 210 patients and DNAR status in only 24. After re-audit of 197 a clear diagnosis was seen in 183 patients, COVID status was documented in 170 patients and DNAR status in 169. Conclusions: Surgical handover is hugely crucial for provision of patient care. Following clear guidance from the royal college of surgeons, better compliance with handover was noted, including a critical improvement in COVID and DNAR status.